A new subfamily of fossorial colubroid snakes from the Western Ghats of peninsular India. Issue 45 (10th December 2018) - Deepak, V.; Ruane, Sara; Gower, David J.
ABSTRACT: We report molecular phylogenetic and dating analyses of snakes that include new mitochondrial and nuclear DNA sequence data for three species of the peninsular Indian endemic Xylophis . The results provide the first molecular genetic test of and support for the monophyly of Xylophis . Our phylogenetic results support the findings of a previous, taxonomically restricted phylogenomic analysis of ultraconserved nuclear sequences in recovering the fossorial Xylophis as the sister taxon of a clade comprising all three recognised extant genera of the molluscivoran and typically arboreal pareids. The split between Xylophis and 'pareids' is estimated to have occurred on a similar timescale to that between most (sub)families of extant snakes. Based on phylogenetic relationships, depth of molecular genetic and estimated temporal divergence, and on the external morphological and ecological distinctiveness of the two lineages, we classify Xylophis in a newly erected subfamily (Xylophiinae subfam. nov.) within Pareidae. urn:lsid:zoobank.org:pub:43BDE72C-6823-4D6A-8601-482862556D78 urn:lsid:zoobank.org:act:AD3486DF-D874-4CFD-8EAE-14FF3E403AF9